When Doctors and Parents Disagree : Ethics, Paediatrics and the Zone of Parental Discretion - Gillam, Lynn; McDougall, Rosalind; Delany , Clare; McDougall, Rosalind; Delany , Clare (Sydney The Federation Press, 2016)
In paediatrics, clinicians and parents sometimes disagree about the appropriate medical treatment for a child. Parents can prefer an option that differs from the clinician$1 (Bs recommendation. When should the parents$1 (Bdecision about their child$1 (Bs medical treatment be overridden? This book explores ethical decision-making when clinicians and parents disagree about medical treatment for a child. It develops and explores a concept called the zone of parental discretion: an ethical tool that aims to balance children$1 (Bs wellbeing and parents$1 (Brights to make medical decisions for their children. Written by experienced clinical ethicists and paediatric clinicians, this book offers ethical analysis and practical guidance based on real-life clinical cases. It aims to assist doctors, nurses, allied health professionals and clinical ethics staff to deal with these ethically challenging situations. The book is divided into five parts: 1. An ethical tool: the zone of parental discretion 2. Roles of doctors and parents in decision-making 3. Clinicians encountering parental refusals 4. Clinicians encountering parental requests for treatment 5. Clinicians encountering parental requests for interventions on healthy childrens
English
Keywords: Ethical issues & debates; parents; doctors; disagree; ethics; paediatrics; parental discretion